MATHEMATICAL LITERACY ABILITY OF CAMPER TYPE STUDENTS BASED ON GENDER DIFFERENCES - Ma'rup Ma'rup; Andi Husniati; Muhammad Rizal Usman; Kristiawati Kristiawati (MaPan : Jurnal Matematika dan Pembelajaran, 2020)
This study illustrated the mathematical literacy ability of camper type students based on gender differences. The subject of this study were class X MIA students of SMAN 2 Takalar. This study is a descriptive study with a qualitative approach design. The data processed is Adversity Quotient data and students’ mathematical literacy abilities data. Adversity Response Profile (ARP) questionnaire was used to find out students with camper type. The test used to see the mathematical literacy ability of male and female students with camper type is PISA (Programme for International Student Assessment) question consists of three questions. Interviews were conducted to further explore students' mathematical literacy ability. Based on the data analysis, it was found that the mathematical literacy ability of the camper type female student was higher than the camper type male student.